1991
DOI: 10.1177/002221949102400205
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Attention Deficit-Hyperactivity Disorder and Learning Disorders

Abstract: This article discusses the relationship between attention deficit-hyperactivity disorder (ADHD) and learning disability (LD). The relevant literature is outlined, and empirical data are presented from a prospective follow-up study of 600 speech/language-impaired children. The data show an increased prevalence of both LD and ADHD among children with early speech/language impairments. Furthermore, LD was strongly associated with ADHD in both the initial and follow-up samples. Also, the children with LD had incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
119
0
6

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(135 citation statements)
references
References 37 publications
6
119
0
6
Order By: Relevance
“…Moreover, the results agree with harpin, 2005 who stated that providing parents with effective strategies to handle homework doing and home instructions with their child's ADHD would seem to be quite important [29]. For the control of aggression in communication, the study revealed highly statistically significant improvement in post and in follow up with p equal 0.002& <0.001 respectively.…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, the results agree with harpin, 2005 who stated that providing parents with effective strategies to handle homework doing and home instructions with their child's ADHD would seem to be quite important [29]. For the control of aggression in communication, the study revealed highly statistically significant improvement in post and in follow up with p equal 0.002& <0.001 respectively.…”
Section: Discussionsupporting
confidence: 86%
“…It is known that perinatal complications, delayed walking, delayed talking, nocturnal enuresis, epilepsy and head injury are associated with an increased prevalence of SpLD and/ or ADHD. [1,3,18,20,21] Microcephaly, flat feet, dysmorphic features, left-handedness and soft neurological signs have been reported to be clinical features which are found 'more often' in children having SpLD and/ or ADHD. [1,3,22] Although these Þ ndings in a child with poor school performance are of some importance, they are not diagnostic of either SpLD or ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of language impairment are reported to reach 24% to 65% in samples of children identified as exhibiting disruptive behaviors (Benasich, Curtiss, & Tallal, 1993) and 59% to 80% of preschool-and schoolage children identified as exhibiting disruptive behaviors also exhibit language delays (Beitchman, Nair, Clegg, Ferguson, & Patel, 1996;Brinton & Fujiki, 1993;Stevenson, Richman, & Graham, 1985). High comorbidity estimates are also reported between language difficulties and diagnoses of ADHD (Cantwell & Baker, 1991;Kim & Kaiser, 2000). Some speech and language problems among a group of children with behavioral social and emotional difficulties are not recognised until later childhood (Giddan, Milling & Campbell, 1996).…”
Section: Can Classroom Sound Field Amplification (Sfa) Play a Causal mentioning
confidence: 99%